Anti-skid dry particle protective glaze, anti-skid marble tile with anti-skid dry particle protective glaze combined with surface three-dimensional textures and preparation method of anti-skid marble tile

By applying anti-slip dry-grain protective glaze on the surface of the tiles, combined with three-dimensional texture design, the magnesium-aluminum spinel raised structure and line-like grooves are formed, which solves the problem of insufficient anti-slip performance of existing anti-slip tiles in water/oil wet conditions, and achieves the combination of high anti-slip performance and good skin feel.

CN119735372AActive Publication Date: 2025-04-01GUANGXI JIANYI CERAMICS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411971072.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-01
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing anti-slip tiles have insufficient anti-slip performance in water/oil wet conditions, and have poor aesthetics and skin feel, making them difficult to manage.

Method used

It adopts anti-slip dry-grain protective glaze, combined with the three-dimensional three-dimensional texture design on the surface, and improves anti-slip performance and skin feel by forming magnesium-aluminum spinel raised structures and linear grooves on the surface of the ceramic tile.

Benefits of technology

Significantly improve anti-slip performance in water/oil environments, while maintaining the aesthetics and skin feel of the tiles for easy care.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735372A_ABST
    Figure CN119735372A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of architectural ceramics, and particularly relates to an anti-skid dry particle protection glaze, an anti-skid marble tile with the anti-skid dry particle protection glaze combined with surface three-dimensional textures and a preparation method of the anti-skid marble tile. The anti-skid dry particle protection glaze comprises basic protection glaze and anti-skid dry particles, and the main component of the anti-skid dry particles is magnesium aluminate spinel; the basic protection glaze is prepared from the following components in percentage by mass: 12 to 18 percent of potassium feldspar, 10 to 22 percent of albite, 2 to 6 percent of wollastonite, 3 to 7 percent of kaolin, 5 to 12 percent of dolomite, 2 to 6 percent of zinc oxide, 6 to 10 percent of aluminum oxide and 15 to 30 percent of high-temperature frit. By optimizing the components of the basic protective glaze, the skin feeling, the color development performance and the like of the glaze surface are improved while the anti-skid and wear-resistant properties are ensured, the skin feeling and the aesthetic feeling of the marble ceramic tile can be reserved to the greatest extent while the anti-skid and wear-resistant properties are ensured by applying the basic protective glaze to the marble ceramic tile and combining with process improvement, and the marble ceramic tile is easier to maintain and is deeply loved by consumers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building ceramics, and in particular to an anti-skid dry particle protective glaze, an anti-skid marble tile with an anti-skid dry particle protective glaze combined with a three-dimensional surface texture, and a preparation method thereof. Background Art

[0002] With the professional segmentation of consumer demand for usage scenarios, such as bathrooms, kitchens, balconies, rooftops and other scenes where water / oil often occurs, the safety performance of ordinary tiles will be significantly reduced in these scenes. Therefore, in these specific scenes, anti-slip performance is the first consideration for consumers.

[0003] Common anti-slip products on the market are generally based on macro-anti-slip structures, such as making grooves on the surface of tiles, or preparing concave-convex design layouts, or using high-temperature dry particles to prepare sand-like rough surfaces, or using wax water to corrode glaze to produce nano-concave-convex structures to increase roughness and improve the anti-slip performance of the product. However, the use of surface grooves or high-temperature dry particles can easily lead to a decrease in the product's transparency, and the higher the anti-slip level, the worse the aesthetic and skin feel of the tiles, and it is also difficult to maintain. The use of wax water to corrode the glaze has a good effect in a dry environment, with a good hand and skin feel, but it is very easy to fail in a water / oil environment.

[0004] Therefore, in scenarios where water / oil is likely to occur, a marble tile product that has excellent anti-slip properties while retaining the product's good skin feel is crucial to people's lives.

[0005] The applicant provided an anti-skid dry particle in the prior application CN 116535246 A, and applied it to the anti-skid glaze on the surface of ceramic tiles. After sintering, the dry particle contains a magnesium-aluminum spinel structure, which can form jagged octahedral spinel protrusions on the surface of the ceramic tile, and has high anti-skid properties even when wet. In addition, when preparing ceramic tiles, the anti-skid glaze is combined with deep ink to have a peeling effect, forming linear grooves on the surface of the ceramic tile. The grooves and protrusions on the surface of the ceramic tile combine to achieve an anti-skid effect. However, the ceramic tiles obtained by this solution have a poor skin feel and are difficult to maintain, which is difficult for some consumers to accept. Summary of the invention

[0006] In view of the above problems, the present invention provides an anti-slip dry particle protective glaze, an anti-slip dry particle protective glaze combined with an anti-slip marble tile with a three-dimensional surface texture, and a preparation method thereof, which improves the skin feel while ensuring anti-slip and wear resistance and is easy to maintain.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A first aspect of the present invention provides an anti-skid dry particle protective glaze, comprising a basic protective glaze and anti-skid dry particles, wherein the main component of the anti-skid dry particles is magnesium-aluminum spinel; the raw materials of the basic protective glaze comprise, by mass percentage, 12-18% potassium feldspar, 10-22% sodium feldspar, 2-6% wollastonite, 3-7% kaolin, 5-12% dolomite, 2-6% zinc oxide, 6-10% aluminum oxide, and 15-30% high-temperature frit; the chemical components of the high-temperature frit comprise, by weight percentage, 45-52% SiO2, 15-20% Al2O3, 1-5% K2O, 2-5% Na2O, 8-10% CaO, 1-2% MgO, 7-8% BaO, and 3-7% ZnO.

[0009] In addition to the above raw materials, a small amount of additives such as sodium tripolyphosphate and sodium carboxymethyl cellulose can be added to the anti-slip dry particle protective glaze to improve the performance of the glaze slurry.

[0010] The anti-skid dry particle protective glaze of the present invention can promote the magnesium-aluminum spinel powder in the anti-skid dry particles to continuously gather and grow on the surface of the tile to develop into a convex structure with diamond-shaped corners during the firing process. At the same time, the magnesium-aluminum spinel in the anti-skid dry particles can also react with quartz and alumina in the glaze to generate a mullite crystal phase, forming a protective layer with high hardness and high wear resistance, protecting the pattern on the surface of the tile from being destroyed. At the same time, the formed glaze layer also has a good skin feel.

[0011] Preferably, the anti-slip dry particles are added in an amount of 10-30% of the weight of the basic protective glaze.

[0012] The second aspect of the present invention provides an anti-slip dry particle protective glaze combined with an anti-slip marble tile with a three-dimensional surface texture, which includes, from bottom to top, a body layer, a base glaze layer, a marble pattern layer, a protective glaze layer, and an anti-slip protective glaze layer. The anti-slip protective glaze layer is composed of an anti-slip dry particle protective glaze layer and a basic protective glaze layer. The anti-slip dry particle protective glaze layer corresponds to the area where the marble texture of the marble pattern layer is located, and the basic protective glaze layer corresponds to the non-texture area of ​​the marble pattern layer; the anti-slip dry particle protective glaze layer is formed by the above-mentioned anti-slip dry particle protective glaze, and the basic protective glaze layer is formed by the basic protective glaze that forms the above-mentioned anti-slip dry particle protective glaze.

[0013] By utilizing the unique texture of marble tiles, the surface anti-skid protective glaze layer is reasonably designed, and the surface protective glaze layer is divided into an anti-skid dry particle protective glaze layer and a basic protective glaze layer according to the marble texture. Anti-skid dry particles containing a magnesium-aluminum spinel structure are introduced into the anti-skid dry particle protective glaze layer. After firing, microscopic serrated octahedral structure protrusions can be formed on the surface of the tile, and can also play a peeling effect. After firing, linear grooves of varying widths and depths appear in the texture area of ​​the tile. Water stains or other liquids on the surface of the tile will be evacuated along the grooves, and the grooves also further enhance the anti-skid effect. In addition to the concave and anti-skid dry particle protective glaze layer, most of the non-texture area on the tile surface is still the basic protective glaze layer. This area is a relatively raised area. When a person steps on it, the sole of the shoe sinks and can contact the relatively concave anti-skid dry particle protective glaze layer. The protrusions of the anti-skid dry particle protective glaze layer can form a pinning effect, thereby having excellent anti-skid performance. Moreover, most areas of the surface anti-slip protective glaze layer are basic protective glaze layers with good skin feel. In this way, the marble tiles not only have good anti-slip properties, but also retain their unique beauty and skin feel to the greatest extent.

[0014] The third aspect of the present invention also provides a method for preparing the anti-slip marble tile, comprising the following steps:

[0015] S01 After the pressed blank is dried, a base glaze is applied on the blank, and then deep ink is sprayed on the base glaze, and then the required marble pattern is printed;

[0016] S02: first printing a layer of protective glaze on the marble pattern, then applying the above-mentioned anti-slip dry granular protective glaze on the marble texture corresponding area of ​​the marble pattern above the protective glaze layer, and then applying the base protective glaze forming the anti-slip dry granular protective glaze on the non-texture corresponding area of ​​the marble pattern;

[0017] S03 firing molding.

[0018] Preferably, in step S02, the anti-slip dry particle protective glaze is applied to the marble texture corresponding area of ​​the marble pattern by using a screen positioning method, so that after firing, a three-dimensional texture effect can be formed on the surface of the tile with the anti-slip dry particles, further improving the anti-slip performance of the tile.

[0019] Preferably, the specific gravity of the anti-slip dry particle protective glaze is 1.30-1.70 g / ml, and the glaze application amount is 120-190 g / m 2 .

[0020] Preferably, the firing and molding surface temperature is ≥1200°C and the time is ≥60min. Too low temperature or too short time may easily lead to incomplete sintering of the brick body. Not only will it affect the physical and chemical properties of the brick body, but also because the basic protective glaze and anti-slip dry particles are not completely sintered, the clarity of the brick surface will be reduced, thereby reducing the ornamental value of this marble tile.

[0021] Preferably, the preparation method of the present invention further comprises step S04, polishing and waxing, so as to better improve the skin feel and facilitate care.

[0022] Preferably, after the polishing treatment, the surface brightness of the base brick is between 25 and 55°.

[0023] Preferably, the polishing first uses 10 groups of 3000 mesh elastic grinding blocks, 10 groups of 800 mesh diamond brush modules, and the pressure is 2kg; 10 groups of sharp 240 mesh sponge polishing, 30 groups of conventional 240 mesh sponge polishing, and the pressure is 0.5kg; for waxing, the wax water uses anti-fouling wax, and the dripping amount is 0.8g / m 2 . Due to the targeted application of protective glaze and dry granular glaze, the brick surface will have a visible three-dimensional texture structure. During the polishing process, the raised parts of the brick surface will be subjected to greater polishing pressure, so the amount of cutting will be greater, the raised parts will be polished smoother, and the skin feel will also improve. The sunken areas will be polished with diamond brushes, and the skin feel will also improve. Applying this polishing treatment to the surface of the tile will make most areas of the tile feel good, and there are relatively fewer grooves in the marble texture area, which will not reduce the skin feel and beauty of the tile while improving the anti-slip performance. Moreover, this polishing process will not excessively damage the original closed pores on the brick surface, so that effective anti-fouling can be achieved by applying a small amount of anti-fouling wax.

[0024] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0025] 1. The anti-skid dry particle protective glaze of the present invention improves the skin feel and color development performance of the glaze surface while ensuring the anti-skid and wear-resistant properties by optimizing the basic protective glaze components.

[0026] 2. The marble tile of the present invention optimizes the basic protective glaze composition and utilizes the unique texture of marble tiles to divide the surface anti-skid protective glaze layer into a relatively concave anti-skid dry particle protective glaze layer and a relatively raised basic protective glaze layer. The combination of these two macroscopic anti-skid structures has a large height difference, which can prevent failure due to water and oil coverage isolation, and has excellent anti-skid performance. At the same time, the overall distribution is mainly based on a large area of ​​skin-feeling basic protective glaze, and the local distribution is supplemented by a small area of ​​anti-skid protective glaze layer, which retains the skin feel and beauty of marble tiles to the greatest extent. Furthermore, combined with process improvements, the obtained tiles have a better skin feel and are easier to care for, which are deeply loved by consumers. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a partial schematic diagram of a marble tile according to an embodiment of the present invention;

[0028] Figure 2 A partial groove display diagram of an embodiment of the present invention;

[0029] Among them: 1-body layer, 2-bottom glaze layer, 3-marble pattern layer, 4-anti-slip protective glaze layer, 41 anti-slip dry particle protective glaze layer, 42-base protective glaze layer, 5, protective glaze layer;

[0030] Figure 3 Schematic diagram of the anti-slip principle of marble tiles according to an embodiment of the present invention. DETAILED DESCRIPTION

[0031] The present invention is further described by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0032] The anti-slip dry particle protective glaze of the present invention and its application in marble tiles are exemplified below.

[0033] The anti-skid dry particle protective glaze of the present invention is obtained by adding anti-skid dry particles into a basic protective glaze. Specifically, the basic protective glaze comprises the following raw materials by mass percentage: 12-18% potassium feldspar, 10-22% sodium feldspar, 2-6% wollastonite, 3-7% kaolin, 5-12% dolomite, 2-6% zinc oxide, 6-10% aluminum oxide, and 15-30% high-temperature frit; the main component of the anti-skid dry particles is magnesium aluminum spinel, and the chemical components of the high-temperature frit comprise by weight percentage: 45-52% SiO2, 15-20% Al2O3, 1-5% K2O, 2-5% Na2O, 8-10% CaO, 1-2% MgO, 7-8% BaO, and 3-7% ZnO.

[0034] A high-temperature frit is provided herein for the preparation of an anti-slip dry particle protective glaze for tiles in the following embodiments: in terms of mass percentage, the chemical composition of the high-temperature frit includes: 51% SiO2, 18% Al2O3, 3% K2O, 3% Na2O, 9% CaO, 1.5% MgO, 7.5% BaO, and 5% ZnO.

[0035] The alumina in the raw material component of the basic protective glaze may be α-type alumina crystals such as corundum, or may be amorphous alumina.

[0036] The raw materials and preparation method of the anti-skid dry particles can refer to the ultra-fine transparent dry materials in CN 116535246 A, which are prepared from the following raw materials: 20-30% magnesite, 35-45% alumina, 2-10% zinc oxide, 15-30% flux and 2-8% catalyst, and the main component is magnesium aluminum spinel. Preferably, the magnesium aluminum spinel component is ≥80wt%.

[0037] Basic protective glaze mainly plays the role of protection, wear resistance, and improving skin feel.

[0038] Preferably, 10-30% of the total weight of the anti-slip dry particles is added to the base protective glaze.

[0039] In addition to the above raw materials, a small amount of additives such as sodium tripolyphosphate and sodium carboxymethyl cellulose can be added to the anti-slip dry particle protective glaze to improve the performance of the glaze slurry.

[0040] The above raw materials are evenly mixed and then ball-milled, and then slurried, iron removed, and sifted to obtain an anti-skid dry particle protective glaze slurry. Since the anti-skid dry particle protective glaze is added with anti-skid dry particles whose main component is magnesium aluminum spinel, after being evenly applied to the surface of the tile, during the firing process, it will continue to gather and grow naturally to form microscopic serrated octahedral structure protrusions, which are relatively small and sharp and cover the surface of the tile. The highly anti-skid ceramic tile prepared by the anti-skid glaze has a high bite force when there are water stains on the surface of the ceramic tile, and the raised octahedral spinel serrated structure on the surface can improve the anti-skid performance of the ceramic tile, is suitable for mass production of ceramic tiles, has stable performance, and has good product quality consistency.

[0041] Moreover, the anti-skid dry-grain protective glaze uses alkaline earth metal oxides as the main additives, and the calcium oxide and magnesium oxide decomposed from dolomite play a solubilizing role; mullite whiskers will be generated at about 1100°C, and the crystal reaction will be completed at 1200°C. Since there are protrusions of spinel structure on the surface of the tile, mullite crystal phase is also generated at the same time, which plays a good protective role on the glaze layer, can improve the hardness and wear resistance of the tile, and at the same time, the long-term anti-skid performance of the tile is good, and it can be maintained for about 30 years without being damaged.

[0042] At the same time, because some glass phase will be generated in the basic protective glaze during the firing stage, it will adhere to the surface of the glaze layer, thereby improving the skin feel and color rendering properties of the glaze layer. The glaze layer obtained by the anti-slip dry particle protective glaze also has a good skin feel and is easy to care for.

[0043] When the anti-skid dry particle protective glaze of the present invention is applied to tiles, an anti-skid marble tile with an anti-skid dry particle protective glaze combined with a three-dimensional texture on the surface can be obtained. Figure 1 The tile comprises, from bottom to top, a body layer 1, a base glaze layer 2, a marble pattern layer 3, a protective glaze layer 5, and an anti-slip protective glaze layer 4. The anti-slip protective glaze layer consists of an anti-slip dry particle protective glaze layer 41 and a basic protective glaze layer 42. The anti-slip dry particle protective glaze layer 41 corresponds to the marble texture area of ​​the marble pattern layer, and the basic protective glaze layer 2 corresponds to the non-texture area of ​​the marble pattern layer. The glaze of the anti-slip dry particle protective glaze layer 41 is formed by adding anti-slip dry particles whose main component is magnesium aluminum spinel to the glaze of the basic protective glaze layer.

[0044] Anti-slip dry particles containing a magnesium-aluminum spinel structure are introduced into the anti-slip dry particle protective glaze layer 41. After firing, microscopic serrated octahedral structure protrusions can be formed on the surface of the tile, and can also have a peeling effect. After firing, linear grooves 41 of varying widths and depths appear in the texture area of ​​the tile. Water stains or other liquids on the surface of the tile will be evacuated along the grooves, and the grooves 41 also further enhance the anti-slip effect.

[0045] Most of the non-textured area on the tile surface is still the basic protective glaze layer 42, which is a raised area relative to the anti-slip dry particle protective glaze layer 41. Figure 3 When a person steps on the sole, the sole sinks and can contact the relatively concave anti-skid dry particle protective glaze layer 41. The protrusions of the anti-skid dry particle protective glaze layer 41 can form a pinning effect. The different applied forces cause the sole to deform and the contact area with the protrusions to increase, thereby improving the anti-skid performance.

[0046] In order to prove the theory, a rubber block was used to test the surface of the tile with the structure. By changing the magnitude of the force applied to the rubber block, the corresponding static friction force and static friction coefficient were measured as shown in Table 1.

[0047] Table 1. Changes of static friction force and static friction coefficient with applied force

[0048] Experiment number Applied force (N) Static friction(N) Static friction coefficient 1# 0 20.7 0.54 2# 10 27.5 0.57 3# 20 36.7 0.63 4# 30 48.5 0.71 5# 40 61.2 0.79

[0049] The feasibility of the ceramic tile structure design theory of the embodiment of the present invention can be proved based on the results in the table.

[0050] Furthermore, since most of the area of ​​the anti-slip protective glaze layer on the surface of the marble tile of the present invention is a basic protective glaze layer with good skin feel, the marble tile not only has good anti-slip performance but also retains its unique beauty and skin feel to the greatest extent.

[0051] It can be seen that the embodiment of the present invention utilizes the unique texture of marble tiles, combines the anti-slip dry particle protective glaze with the three-dimensional surface texture, and reasonably designs the marble tiles with good skin feel and aesthetics as well as anti-slip effect.

[0052] The blank layer 1 in the tile can be pressed from any conventional blank on the market, the base glaze layer 2 can be formed using the base glaze commonly used in marble tiles, and the protective glaze layer 5 can also use a glaze such as the basic protective glaze layer 42, or different protective glazes can be selected according to needs.

[0053] The method for preparing the anti-slip marble tile according to the embodiment of the present invention specifically comprises the following steps:

[0054] After the pressed body of S01 is dried, a base glaze is applied on the body, and then deep ink is sprayed on the base glaze, and then the required marble pattern is printed.

[0055] The blank in this scheme can be pressed from any conventional blank on the market. In different embodiments, the raw materials of the blank can be adaptively adjusted. Here is a group of blanks for the preparation of ceramic tiles in the following embodiments: in terms of mass percentage, the chemical composition of the blank powder includes: SiO2 65.88%, Al2O3 20.32%, Fe2O3 0.7%, TiO20.16%, CaO 0.51%, MgO 0.91%, K2O 3.73%, Na2O 2.65% and loss on ignition 4.83%.

[0056] Similarly, the base glaze can also be any base glaze on the market. The fineness of the base glaze can be less than 0.6% on a 325-mesh sieve, the specific gravity is 1.80-1.87 g / ml (1.83 g / ml in the following embodiments), and the glaze amount is 300-380 g / m 2 (The following examples are 350g / m 2 ), a set of base glazes are provided herein for the preparation of tiles in the following embodiments: in terms of mass percentage, the chemical composition of the base glaze includes: SiO2 49.32%, Al2O3 20.53%, Fe2O3 0.15%, TiO2 0.08%, ZnO 2.32%, CaO4.21%, MgO 3.65%, K2O 3.53%, Na2O 2.76%, BaO 3.24%, ZrO 25.74% and loss on ignition 4.36%.

[0057] Preferably, after the green body is dried, the moisture content can be controlled at 0.3-0.5wt% before the base glaze is applied.

[0058] A high-definition digital inkjet machine can be used to print linear engraving ink, and the engraving ink is printed on the area where the marble pattern is located; the engraving ink can be the engraving functional ink produced by Yidajia Company.

[0059] S02 firstly prints a layer of protective glaze on the marble pattern, then applies anti-skid dry granule protective glaze on the area corresponding to the marble texture of the marble pattern above the protective glaze layer, and then applies basic protective glaze on the area corresponding to the non-texture; the anti-skid dry granule protective glaze is formed by adding anti-skid dry granules whose main component is magnesium aluminum spinel to the basic protective glaze;

[0060] A layer of protective glaze is first printed to protect the marble pattern below. The glaze composition of the protective glaze and the basic protective glaze forming the anti-slip dry particle protective glaze can be the same or different, and those skilled in the art can choose according to needs.

[0061] In a preferred embodiment, in step S02, the anti-slip dry particle protective glaze is applied to the dark ink texture area using a screen positioning method, so that after firing, a three-dimensional texture effect can be formed on the surface of the tile with the dry particle glaze, further improving the anti-slip performance of the tile.

[0062] In a preferred embodiment, the specific gravity of the anti-slip dry particle protective glaze is 1.30-1.70 g / ml, and the glaze application amount is 120-190 g / m 2 .

[0063] S03 firing molding.

[0064] Firing temperature that is too low or time that is too short can easily lead to incomplete sintering of the brick body; not only will it affect the physical and chemical properties of the brick body, but also because the protective glaze and anti-slip dry particles are not completely sintered, it will also reduce the clarity of the brick surface and reduce the ornamental value of the marble tile.

[0065] In a preferred embodiment, the firing molding surface temperature is ≥1200°C and the time is ≥60min. In a specific embodiment, the ceramic tile is dried in a drying oven at 120-180°C for 30-60min, and then fired in a kiln at 1180-1220°C for 65-75min. After edge grinding, the anti-slip marble tile is obtained.

[0066] Furthermore, the preparation method of the present invention also includes step S04, polishing and waxing, so as to better improve the skin feel and facilitate care.

[0067] Preferably, after the polishing treatment, the surface brightness of the base brick is between 25 and 55°.

[0068] Preferably, the polishing first uses 10 groups of 3000 mesh elastic grinding blocks, 10 groups of 800 mesh diamond brush modules, and the pressure is 2kg; 10 groups of sharp 240 mesh sponge polishing, 30 groups of conventional 240 mesh sponge polishing, and the pressure is 0.5kg; for waxing, the wax water uses anti-fouling wax, and the dripping amount is 0.8g / m 2 . Due to the targeted application of the basic protective glaze and the anti-slip dry particle protective glaze, the brick surface will have a visible three-dimensional texture structure. During the polishing process, the raised parts of the brick surface will be subjected to greater polishing pressure, so the amount of cutting will be greater, the raised parts will be polished smoother, and the skin feel will also improve. The sunken areas will be polished with diamond brushes, and the skin feel will also improve. Applying this polishing treatment to the surface of the tile will make most areas of the tile feel good, and there are relatively few grooves in the marble texture area, which will not reduce the skin feel and beauty of the tile while improving the anti-slip performance. Moreover, this polishing process will not excessively damage the original closed pores on the brick surface, so that effective anti-fouling can be achieved by applying a small amount of anti-fouling wax.

[0069] The following is further described in conjunction with specific embodiments.

[0070] The anti-skid dry particles used in the following examples have a magnesium-aluminum spinel content of ≥80 wt %;

[0071] The deep ink is selected from the deep functional ink produced by Yidajia Company;

[0072] The polishing blocks are all from Jiangmen Shuangyi Abrasives Company.

[0073] 1. Basic protective glaze screening

[0074] Example 1-1

[0075] A non-slip marble tile, the preparation method of which is as follows:

[0076] The S01 green body powder is pressed and formed by Henglitai press to obtain brick green body. The brick green body is dried in a drying kiln, and the moisture content is controlled at 0.3-0.5% before being coated with base glaze. After that, a high-definition digital inkjet machine is used to print deep ink, and the ink area is designed according to the marble pattern texture. A high-definition digital inkjet machine is used to print marble patterns, giving the tile surface a rich stone texture.

[0077] S02 uses a screen printing process to print a protective glaze over the marble pattern;

[0078] S03 Dry in a drying oven at 120-180℃ for 30-60min, then place in a kiln and burn at 1180-1220℃ for 65-75min.

[0079] S04 After edge grinding, the anti-slip marble tile is obtained.

[0080] The protective glaze is made by mixing and ball-milling the following raw materials by mass percentage: 22% albite, 25% potassium feldspar, 4% zinc oxide, 13% barium carbonate, 7% kaolin, 15% wollastonite, 6% alumina, and 8% calcined clay. The specific gravity of the protective glaze is 1.4g / ml, and the glaze amount is 135g / m 2 .

[0081] Example 1-2

[0082] A non-slip marble tile, the preparation method of which is as follows:

[0083] The S01 green body powder is pressed and formed by Henglitai press to obtain brick green body. The brick green body is dried in a drying kiln, and the moisture content is controlled at 0.3-0.5% before being coated with base glaze. After that, a high-definition digital inkjet machine is used to print deep ink, and the ink area is designed according to the marble pattern texture. A high-definition digital inkjet machine is used to print marble patterns, giving the tile surface a rich stone texture.

[0084] S02 uses a screen printing process to print a layer of non-slip dry-grain protective glaze on top of the marble pattern;

[0085] S03 Dry in a drying oven at 120-180℃ for 30-60min, then place in a kiln and burn at 1180-1220℃ for 65-75min.

[0086] S04 After edge grinding, the anti-slip marble tile is obtained.

[0087] The anti-skid dry particle protective glaze is obtained by adding 20wt% anti-skid dry particles to the protective glaze in Example 1-1, with a specific gravity of 1.4g / ml and a glazing amount of 135g / m 2 .

[0088] Examples 1-3

[0089] An anti-slip marble tile with an anti-slip dry particle protective glaze combined with a three-dimensional surface texture, and a preparation method thereof is as follows:

[0090] S01 green body powder is pressed and formed by Henglitai press to obtain brick green body, which is then dried in drying kiln, and the moisture content is controlled at 0.3-0.5% before being coated with base glaze. After that, a high-definition digital inkjet machine is used to print deep ink, and the ink area is designed according to the marble pattern texture; the high-definition digital inkjet machine is used to print marble pattern, so that the surface of the tile has a rich stone texture;

[0091] S02 uses screen printing technology to print a layer of non-slip dry-grain protective glaze above the marble pattern;

[0092] S03 is dried in a drying oven at 120-180℃ for 30-60min, and then fired in a kiln at 1180-1220℃ for 65-75min;

[0093] S04 After edge grinding, the anti-slip marble tile is obtained.

[0094] There are differences from the anti-skid dry particle protective glaze used in Example 1-2, that is, this embodiment adopts a preferred basic protective glaze, and the raw materials are different from the conventional protective glaze. Measured by mass percentage, the basic protective glaze includes the following raw materials mixed and ball-milled: 17% potassium feldspar, 20% sodium feldspar, 4% wollastonite, 6% kaolin, 8% dolomite, 6% zinc oxide, 9% aluminum oxide, and 30% high-temperature frit; 20wt% of anti-skid dry particles are added to the basic protective glaze to obtain the anti-skid dry particle protective glaze of Example 1-3. After ball-milling, the anti-skid dry particle protective glaze is adjusted to a specific gravity of 1.45g / ml with water, and the glazing amount is 140g / m 2 .

[0095] The prepared tiles were subjected to performance testing, and the specific test results are shown in Table 2:

[0096] Table 2 Test results of ceramic tile samples in Example 1

[0097]

[0098]

[0099] Note: The national standard GBT4100-2015 is used to test the static friction coefficient when the tile surface is dry, and the German standard DIN51130:2014 inclined platform method is used to test the anti-slip performance in the presence of water or oil on the soles.

[0100] Anti-fouling test: 1. Wipe the surface of the tile clean, put it into a 200℃ drying oven and dry it for 20 minutes before taking it out; 2. Use a blue oil-based marker to apply pattern marks on the dried tile surface; 3. Use a wet towel to wipe the blue pattern marks, and observe from a distance of 50cm to see if there are any stains left; 4. Repeat the test 3 times and observe at a distance of 50cm. If there are no stains left in 3 times, it is considered qualified. If there are a small amount of stains left, it is considered slight hidden stains, and if there are a large number of stains left, it is considered hidden stains.

[0101] It can be seen from the test results in the above table that compared with ordinary protective glazes, this solution optimizes the basic protective glaze composition. After using it on the tile surface, it can improve the hardness and wear resistance of the tiles, while still maintaining good anti-fouling performance. The texture and pattern of the tiles have better color development and also have a better skin feel.

[0102] 2. Process Optimization

[0103] Example 2-1

[0104] An anti-slip marble tile with an anti-slip dry particle protective glaze combined with a three-dimensional surface texture, and a preparation method thereof is as follows:

[0105] S01 green body powder is pressed and formed by Henglitai press to obtain brick green body, which is then dried in drying kiln, and the moisture content is controlled at 0.3-0.5% before being coated with base glaze. After that, a high-definition digital inkjet machine is used to print deep ink, and the ink area is designed according to the marble pattern texture; the high-definition digital inkjet machine is used to print marble pattern, so that the surface of the tile has a rich stone texture;

[0106] S02 adopts screen printing technology, first printing a layer of protective glaze on the marble pattern, then screen printing anti-slip dry granular protective glaze on the area corresponding to the marble texture, and then printing the basic protective glaze on the non-texture corresponding area;

[0107] S03 is dried in a drying oven at 120-180℃ for 30-60min, and then fired in a kiln at 1180-1220℃ for 65-75min;

[0108] S04 polishing and waxing, the polishing process first uses 10 sets of 3000 mesh elastic grinding blocks, 10 sets of 800 mesh diamond brush modules, and the pressure is 2kg; then 10 sets of sharp 240 mesh sponge polishing, 30 sets of conventional 240 mesh sponge polishing, the pressure is 0.5kg; the wax water uses anti-fouling wax, and the dripping amount is 0.8g / m 2 After polishing, the surface brightness of the base brick is between 25 and 55°.

[0109] The anti-skid dry particle protective glaze is the same as the basic protective glaze in Examples 1-3, wherein the amount of anti-skid dry particles added is 20% of the weight of the basic protective glaze. The anti-skid dry particle protective glaze is ball-milled and water is added to adjust the specific gravity to 1.45 g / ml. The glaze amount is 140 g / m 2 .

[0110] Example 2-2

[0111] The preparation steps and parameters in this example are the same as those in Example 2-1, except that the amount of anti-slip dry particles added to the anti-slip dry particle protective glaze is changed to 10%.

[0112] Example 2-3

[0113] The preparation steps and parameters in this embodiment are the same as those in Embodiment 2-1, except that the amount of anti-slip dry particles added to the anti-slip dry particle protective glaze is changed to 30%.

[0114] Embodiment 2-4

[0115] All preparation steps and parameters in this embodiment are the same as those in Embodiment 2-1, except that step S02 is modified.

[0116] S02 uses screen printing technology. A layer of protective glaze is printed on the top of the marble pattern, and then a narrow texture area is selected in the corresponding area of ​​the marble texture to screen print the anti-slip dry particle protective glaze, and then the basic protective glaze is printed in the non-texture corresponding area.

[0117] Embodiment 2-5

[0118] All preparation steps and parameters in this embodiment are the same as those in Embodiment 2-1, except that step S02 is modified.

[0119] S02 uses screen printing technology. A layer of protective glaze is printed on the top of the marble pattern, and then a wide texture area is selected in the corresponding area of ​​the marble texture to screen print the anti-slip dry particle protective glaze, and then the basic protective glaze is printed in the non-texture corresponding area.

[0120] Embodiment 2-6

[0121] All preparation steps and parameters in this embodiment are the same as those in Embodiment 2-1, except that step S04 is modified.

[0122] S04. Polishing process: first use 10 sets of 3000 mesh elastic grinding blocks with a pressure of 2kg; then use 10 sets of sharp 240 mesh sponges and 30 sets of regular 240 mesh sponges with a pressure of 0.5kg; wax water uses anti-fouling wax with a drop coating amount of 0.8g / m 2 .

[0123] Embodiment 2-7

[0124] All preparation steps and parameters in this embodiment are the same as those in Embodiment 2-1, except that step S04 is modified.

[0125] S04. Polishing process: first use 10 sets of 800 mesh diamond brush modules with a pressure of 2kg; then 10 sets of sharp 240 mesh sponges and 30 sets of regular 240 mesh sponges with a pressure of 0.5kg; wax water uses anti-fouling wax with a drop coating amount of 0.8g / m 2 .

[0126] The performance of each tile sample in the embodiment was tested, and the results are shown in Table 2.

[0127] Table 2 Performance test results of Example 2

[0128]

[0129]

[0130] From the test results in the above table, it can be seen that by further optimizing the dosage of the basic protective glaze component, the dosage of the anti-slip dry particle component, the silk-screen area and the polishing process of the anti-slip dry particle protective glaze, the anti-slip grade of the marble tile can reach R12, the hardness can reach level 8, and the wear resistance level can reach level 4 (6000 revolutions). At the same time, it also has excellent anti-fouling properties, coloring effects, good skin feel and easy care.

[0131] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0132] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An anti-slip dry particle protective glaze, characterized in that: It comprises a basic protective glaze and anti-skid dry particles, wherein the main component of the anti-skid dry particles is magnesium-aluminum spinel; the raw materials of the basic protective glaze comprise, by mass percentage, 12-18% potassium feldspar, 10-22% sodium feldspar, 2-6% wollastonite, 3-7% kaolin, 5-12% dolomite, 2-6% zinc oxide, 6-10% aluminum oxide, and 15-30% high-temperature frit; the chemical components of the high-temperature frit comprise, by weight percentage, 45-52% SiO2, 15-20% Al2O3, 1-5% K2O, 2-5% Na2O, 8-10% CaO, 1-2% MgO, 7-8% BaO, and 3-7% ZnO.

2. The anti-slip dry particle protective glaze according to claim 1, characterized in that: The anti-skid dry particles are added in an amount of 10-30% of the weight of the basic protective glaze.

3. A non-slip marble tile with non-slip dry granular protective glaze combined with a three-dimensional surface texture, characterized in that: From bottom to top, it includes the body layer, base glaze layer, marble pattern layer, protective glaze layer, and anti-slip protective glaze layer. The anti-skid protective glaze layer is composed of an anti-skid dry particle protective glaze layer and a base protective glaze layer. The anti-slip dry particle protective glaze layer corresponds to the area where the marble texture of the marble pattern layer is located, and the basic protective glaze layer corresponds to the non-texture area of ​​the marble pattern layer; the anti-slip dry particle protective glaze layer is formed by the anti-slip dry particle protective glaze as described in claim 1 or 2, and the basic protective glaze layer is formed by the basic protective glaze that forms the anti-slip dry particle protective glaze as described in claim 1 or 2.

4. The method for preparing the anti-skid marble tile with anti-skid dry particle protective glaze combined with a three-dimensional surface texture as claimed in claim 3, characterized in that: The steps include: S01 After the pressed blank is dried, a base glaze is applied on the blank, and then deep ink is sprayed on the base glaze, and then the required marble pattern is printed; S02: first printing a layer of protective glaze on the marble pattern, then applying the anti-slip dry granular protective glaze as claimed in claim 1 or 2 on the marble texture corresponding area of ​​the marble pattern above the protective glaze layer, and then applying the base protective glaze as claimed in claim 1 or 2 on the non-texture corresponding area of ​​the marble pattern; S03 firing molding.

5. The preparation method according to claim 4, characterized in that: In the step S02, the anti-slip dry particle protective glaze is applied to the area corresponding to the marble texture of the marble pattern by using a screen positioning.

6. The preparation method according to claim 4, characterized in that: The specific gravity of the anti-slip dry particle protective glaze is 1.30-1.70g / ml, and the glaze application amount is 120-190g / m 2 .

7. The preparation method according to claim 4, characterized in that: The sintering molding surface temperature is ≥1200°C and the sintering time is ≥60min.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The method also includes step S04, polishing and waxing.

9. The preparation method according to claim 8, characterized in that: After the polishing treatment, the surface brightness of the base brick is between 25 and 55 degrees.

10. The preparation method according to claim 9, characterized in that: The polishing first uses 10 groups of 3000 mesh elastic grinding blocks and 10 groups of 800 mesh diamond brush modules with a pressure of 2kg; then, 10 groups of sharp 240 mesh sponges and 30 groups of conventional 240 mesh sponges are used for polishing with a pressure of 0.5kg; for waxing, anti-fouling wax is used for the wax water, and the dripping amount is 0.8g / m 2 .

Citation Information

Patent Citations

  • Dry particle protective glaze, soft light marble tile and preparation method of soft light marble tile

    CN115448598A

  • Wax ceramic tile with three-dimensional decorative effect and preparation method thereof

    CN115677220A

  • High-skid-resistance transparent dry granules, skid-resistance glaze using same, high-skid-resistance ceramic tile with hydrophobic function and preparation method of high-skid-resistance transparent dry granules

    CN116535246A

  • Ultra-white body porcelain tile with pearlescent soft light and preparation method of ultra-white body porcelain tile

    CN116924783A

  • Protective glaze, stone-like ceramic tile and preparation method of stone-like ceramic tile

    CN117567030A